New Hebrews: making national culture in Zion - Peleg, Yaron (Cambridge University Press, 2025)
"Examines the cultural history of Zionism and the revolutionary ways it used language, literature, architecture, art, music and body culture to reshape modern Jewish culture. Yaron Peleg offers an interdisciplinary study of nationalism and examines the psychology of modern Israel. This title is also available as open access on Cambridge Core"-- Provided by publisher